Placenta praevia: Preach and perception - Tan KC,; Chuah CY,; Fong KY,; Nor Azlin MI,; Phang SL, (Penerbit UKM, 2007)
Placenta praevia is a known obstetric condition that causes complications to mother and fetus. This study was done to evaluate the knowledge of placenta praevia amongst the obstetric patients. A cross sectional study was carried out in Hospital Ipoh, Perak among 323 antenatal and postnatal patients. Socio-demographic parameters (ie age, race, parity, occupation, educational level) and history of placenta praevia were studied in relation to level of knowledge and attitude towards placenta praevia. Twenty (6.2%) from 323 women had current or past history of placenta praevia. Three had history of placenta praevia while 17 had current placenta praevia with prevalence of 5.3%. The mean score of knowledge achieved by patients was 11.8 which indicated overall poor knowledge. Occupation, level of education and history of placenta praevia were found to have a relationship with level of knowledge regarding placenta praevia in all obstetric patients. There was a significant relationship between attitude of patients with current and history of placenta praevia to level of knowledge regarding placenta praevia. (p=0.037, <0.05). In conclusion, the knowledge and attitude towards placenta praevia among obstetric patients in Hospital Ipoh was better in those who had higher education status, white-collar occupation and currently pregnant with placenta praevia